Zen na poddaszu. Przyczynek do recepcji buddyzmu w Polsce - Tracz, Bogusław (Polska 1944/45-1989. Studia i Materiały, 2019)
Artykuł jest próbą przedstawienia dziejów recepcji buddyzmu w powojennej Polsce, jako elementu przenikania nad Wisłę zjawisk charakterystycznych dla cywilizacji zachodniej (atlantyckiej) w drugiej połowie XX w. Przedstawione zostały główne, pozauniwersyteckie ośrodki i grupy, w których podejmowano próby praktyk buddyjskich, oraz osoby, które przyczyniły się do popularyzacji różnych odmian buddyzmu, ze szczególnym uwzględnieniem nurtu zen i roli, jaką w jego rozpowszechnianiu w Polsce odegrał amerykański nauczyciel buddyzmu zen, Philip Kapleau. Przedstawiono również działania prowadzone przeciwko polskim buddystom przez policję polityczną oraz drogę prowadzącą do rejestracji i tym samym zalegalizowania działalności pierwszej wspólnoty buddyjskiej w Polsce, co nastąpiło dopiero w 1981 r. Zen in the attic. A contribution to the reception of Buddhism in Poland The reception of Buddhism, which in Europe began already in the nineteenth century, did not pass over Poland. Initially limited to scientific milieus and small social circles, in time Buddhism became more widely present, especially in artistic communities and youth subculture groups. After the World War Second, despite of being cut off by the Iron Curtain from main cultural changes, Poland was permeated by fashions and phenomena characteristic of the Atlantic civilisation, including the fascination for Oriental religiosity, especially Buddhism. Oriental studies were carried out at universities, while individuals and groups of enthusiasts tried on their own to study Buddha’s writings and teachings. There were among those people Władysław Misiewicz from Radom and Piotr Boniński from Gliwice. Their interest, however, was limited to intellectual reflection and they did not practice Buddhism. One of the first groups to practice Buddhist meditation was the circle of artist Andrzej Urbanowicz, who in 1967, together with his friends established an artistic group called “Oneiron”. Texts and intellectual quest led them towards Zen Buddhism, and Urbanowicz’s atelier became the first place in Poland where meditation was practiced. Meetings were also held at Mąchocice Kapitulne near Kielce. Activities of the still unformal group of Buddhists were kept under surveillance by the secret police. In 1975 Philip Kapleau, an American teacher of Buddhism, answered the group’s invitation, and from that time on, he visited Poland many a time. After Urbanowicz left Poland, in 1978, architect Andrzej Korbel became the leader of the group; in time, the Warsaw circle took the lead, with psychotherapist Wojciech Eichelberger. In the meantime, however, efforts to legalise the group encountered obstacles and it was not until 1981 that the first Zen Buddhist Community in Poland was established. Later on, next groups were organised but, despite the fact that a real breakthrough took place after 1989, already in the 1980s there were four officially registered Buddhist communities, with branches and circles in different towns and cities.